Research Trend of Computational Thinking in Phiysics Learning: a Bibliometric Analysis from 2015 to 2024 - Riskawati, Riskawati; Rusdiana, Dadi; Abdurrahman, Abdurrahman; Hendra, Hendra (Jurnal Pendidikan Progresif, 2025)
Research Trend of Computational Thinking in Phiysics Learning: a Bibliometric Analysis from 2015 to 2024. This study performs bibliometric analysis to examine research development on CT in physics education for the years spanning 2015-2024. Objective: The study seeks to outline the research and intellectual history of Computation Thinking (CT) integration within a specific framework by examining its spatial development in terms of the primary contributors CT’s development through analyzing cumulative research, leading journals, contributing countries, dominant scholars, thematic networks and the changes of key topics over time. Methods: From the Scopus database, 345 peer-reviewed journal articles were selected. To visualize research networks, VOSviewer was used, while Bibliometrix in R Studio was used to analyze publication trends, author contributions, journal impact, citations, and assess the citation patterns of work over time. Findings: From the Scopus database, a total of 345 peer-reviewed journals were selected. The quantitative data analysis involving visualization of research networks was done using VOSviewer, while Bibliometrix (R Studio) was used for evaluation of publication and author contributions in relation to impact, citation, and trends. Findings indicate significant growth in research focused on Computational Thinking (CT) in Physics Education, with an overarching 33.86% annual increase, peaking in 2023. The research covers 156 journals, with the most prolific being Education and Information Technologies. The evaluation emphasized the exceptional worldwide collaboration with 1,216 authors from countries like the United States, Indonesia, and China. Intent phrase clusters included “computational thinking”, “augmented reality”, and “STEM education” indicating an emphasis on the integration of CT with advanced technologies. The evolution of themes indicates movement from STEM simulations to more expansive virtual reality and critical thinking. Conclusions: The advancements in physics education and students' problem-solving skills, as well as teaching innovations through International collaborations, have begun using Computational Thinking CT). Keywords: computational thinking, physics education, bibliometric analysis, vosviewer, bibliometrix.